Drugi, trzeci, czwarty… Poszukiwanie sensu pracy pedagoga specjalnego w różnych estetykach wychowawczych - Podgórska-Jachnik, Dorota (Wydawnictwo Naukowe UAM, 2013)
The article is inspired by Professor Lech Witkowski’s Edukacja wobec sporów o (po)nowoczesność (2007) and his concept of different aesthetics of the educational situation. This concept refl ects a certain way of looking at the ontological forms and styles of behavior and complex social forms, also in the educational situation. Education aesthetics specify a different relation between the teacher and the student. Witkowski asks what it means that the counselor is “fi rst”, ”second”, “third”, “fourth” etc. to the pupil. The author of this article applies this question to the situation of the special counselor and all special pedagogy. Using sequence numbers cannot be associated with competition here, and different aesthetics are not evaluated in any form. Similarly, special pedagogy does not aspire to the dominant position in the educational system, deliberately seeking self-restraint, but at the same time it does not reject the validity of its importance. The analysis looks for the signifi cance of the special counselor’s activities in various aesthetic confi gurations of social relations between the teacher and the pupil, to make the most of their resources, to be aware of the risks involved, and to consciously accept educational challenges.
Second, Third, Fourth… Looking for the Sense of a Special Counselor’s Work in Various Educational Aesthetics
Keywords: education; upbringing; aesthetics; special pedagogy; theory of education; teacher-pupil